(untitled) (CIPEEX, 2025)
The proposed social media monitoring and publishing system for a biblical institution in Anápolis represents a significant innovation in the field of social media management. Specifically targeted at biblical course institutions, the system is tailored to address a niche market often overlooked by more generic tools. It offers several unique features that enhance user experience and expand its adaptability for different types of users. Among its most notable features are automated content scheduling, monitoring, and detailed reports. What sets this system apart is its ability to cater to different types of users while maintaining a specialized focus on the needs of biblical institutions. This flexibility significantly increases the market potential, as businesses can use it to strengthen their brand, while politicians can harness it to optimize their campaigns. On the technology front, the system incorporates advanced data analysis algorithms and artificial intelligence to enhance post optimization and recommend better engagement strategies. Its user-friendly interface ensures that users, regardless of their social media management experience, can navigate and utilize the platform with ease. This level of usability is crucial in ensuring a high adoption rate, contributing to the overall success of the system. In terms of validating the system’s efficacy, the development team used the Design Thinking methodology. This process involved detailed discussions with the biblical institution that requested the project, alongside broader market research. The insights gained allowed the team to identify key challenges and refine the system’s capabilities to meet these specific needs. Furthermore, research into how similar solutions are implemented in the market revealed gaps that this system effectively fills. This methodical approach to validation not only helped fine-tune the initial concept but also demonstrated the system’s viability in a broader market. The system’s impact extends beyond improving social media management. By automating routine tasks, providing detailed insights, and streamlining event promotion, the system saves time and resources for institutions. Its potential market reach is broad, encompassing educational institutions, businesses, and political campaigns, as social media continues to be a vital tool for engaging target audiences. Overall, the proposed system distinguishes itself through its customization, advanced technology, and thorough validation, positioning it as an innovative solution that meets current and future demands in the social media management market.